Anthropocence Realism Fiction in the Age of Climate Change - Thieme, John (2024)
The book considers the poetics of twenty-first century climate change fiction, focusing on realism and exploring the realist mode as a means to engage readers with what is without doubt one of, if not the, most pressing problem of our day: climate change